Humanistic Heritage - Schwarz, Daniel R. author. aut Link
VIII, 282 p.
Keywords: This is an examination of the principle works of Anglo-American novel criticism, defining the values, method and concepts that these works have in common and advancing a defence of Anglo-American humanistic criticism and the ideas proposed by Structuralism, Marxism and deconstruction.